Context-dependent transcriptional regulations of YAP/TAZ in cancer. (28th February 2022) - Guo, Yibo; Luo, Juan; Zou, Hailin; Liu, Chenxin; Deng, Liang; Li, Peng
Abstract: As the downstream effectors of Hippo pathway, YAP/TAZ are identified to participate in organ growth, regeneration and tumorigenesis. However, owing to lack of a DNA-binding domain, YAP/TAZ usually act as coactivators and cooperate with other transcription factors or partners to mediate their transcriptional outputs. In this article, we first present an overview of the core components and the upstream regulators of Hippo-YAP/TAZ signaling in mammals, and then systematically summarize the identified transcription factors or partners that are responsible for the downstream transcriptional output of YAP/TAZ in various cancers. Highlights: Hippo-YAP/TAZ signalling is a master regulator for cell proliferation and organ size control in mammals. Deregulation of Hippo-YAP/TAZ signalling is implicated in various cancers. YAP-TEAD complex is not sufficient to execute all transcriptional programs in different contexts. The transcriptional regulations of YAP/TAZ are dependent on the interacting partners in cancers.